All-solid battery
Patent Information
- Application Number
- JP2024224333
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-10-12
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-14
AI Technical Summary
【0014】 本発明に関する全固体電池は、蓄電素子と水分との接触を抑制すること、及び、蓄電素子から発生したガスを吸収できることの少なくとも一方を実現できる。
Smart Images

Figure 2025036461000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an all-solid-state battery. [Background technology]
[0002] Patent Document 1 discloses an example of an all-solid-state battery. This all-solid-state battery includes an electric storage element including a positive electrode layer, a negative electrode layer, and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer, and an electrically insulating frame disposed around the electric storage element. The electric storage element and the electrically insulating frame are housed in a battery case. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2009-193728 A Summary of the Invention [Problem to be solved by the invention]
[0004] In the above-mentioned all-solid-state battery, water vapor, which is an example of gas, may enter from the outside of the battery case. When moisture contained in the water vapor comes into contact with the solid electrolyte layer, gas such as hydrogen sulfide may be generated depending on the type of solid electrolyte used in the solid electrolyte layer. This problem is not limited to the case where moisture comes into contact with the solid electrolyte layer, but also occurs when, for example, the positive electrode layer and the negative electrode layer contain a solid electrolyte and moisture comes into contact with the solid electrolyte contained in the positive electrode layer and the negative electrode layer.
[0005] An object of the present invention is to provide an all-solid-state battery capable of at least one of suppressing contact between an electricity storage element and moisture and absorbing gas generated from the electricity storage element. [Means for solving the problem]
[0006] An all-solid-state battery according to a first aspect of the present invention comprises: an electricity storage element including a solid electrolyte; and a resin film for an all-solid-state battery arranged so as to be in contact with at least a part of the solid electrolyte, wherein the resin film for an all-solid-state battery includes at least one of a water absorbing agent and a gas absorbing agent.
[0007] An all-solid-state battery according to a second aspect of the present invention is the all-solid-state battery according to the first aspect, further comprising a solid electrolyte layer containing the solid electrolyte, and the resin film for all-solid-state batteries is disposed so as to be in contact with at least the solid electrolyte layer.
[0008] An all-solid-state battery according to a third aspect of the present invention is the all-solid-state battery according to the first or second aspect, further comprising a positive electrode layer containing the solid electrolyte, and the resin film for all-solid-state batteries is disposed so as to be in contact with at least the positive electrode layer.
[0009] An all-solid-state battery according to a fourth aspect of the present invention is the all-solid-state battery according to any one of the first to third aspects, comprising an anode layer containing the solid electrolyte, and the resin film for all-solid-state batteries is disposed so as to be in contact with at least the anode layer.
[0010] An all-solid-state battery according to a fifth aspect of the present invention is the all-solid-state battery according to any one of the first to fourth aspects, wherein the resin film for an all-solid-state battery has a frame shape surrounding the solid electrolyte.
[0011] An all-solid-state battery according to a sixth aspect of the present invention is the all-solid-state battery according to any one of the first to fifth aspects, comprising an exterior body that seals the energy storage element, the exterior body being constituted by a film-like exterior member including a barrier layer, and the all-solid-state battery resin film being disposed at least in a portion on the inside of the barrier layer.
[0012] An all-solid-state battery according to a seventh aspect of the present invention is the all-solid-state battery according to any one of the first to sixth aspects, wherein the gas absorbent includes at least one selected from the group consisting of a sulfur-based gas chemical absorbent and a sulfur-based gas physical absorbent.
[0013] An all-solid-state battery according to an eighth aspect of the present invention is the all-solid-state battery according to the seventh aspect, wherein the sulfur-based gas chemical absorbent is a metal oxide, or an inorganic material carrying or containing a metal or metal ions. Effect of the Invention
[0014] The all-solid-state battery according to the present invention can achieve at least one of suppressing contact between the electricity storage element and moisture and absorbing gas generated from the electricity storage element. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 is a plan view of an all-solid-state battery according to an embodiment. [Diagram 2] FIG. 2 is a cross-sectional view showing an example of a layer structure of the exterior member of FIG. [Diagram 3] Cross-sectional view taken along line D3-D3 in Figure 1. [Figure 4] FIG. 4 is a plan view of the resin film for the all-solid-state battery of FIG. 3. [Diagram 5] FIG. 4 is a cross-sectional view showing another arrangement example of the resin film for the all-solid-state battery shown in FIG. 3 . [Figure 6] FIG. 4 is a cross-sectional view showing still another arrangement example of the resin film for the all-solid-state battery shown in FIG. 3 . [Figure 7] FIG. 4 is a cross-sectional view showing still another arrangement example of the resin film for the all-solid-state battery shown in FIG. 3 . [Figure 8] FIG. 4 is a cross-sectional view showing still another arrangement example of the resin film for the all-solid-state battery shown in FIG. 3 . [Figure 9] FIG. 4 is a cross-sectional view showing still another arrangement example of the resin film for the all-solid-state battery shown in FIG. 3 . [Figure 10] FIG. 4 is a cross-sectional view showing still another arrangement example of the resin film for the all-solid-state battery shown in FIG. 3 . [Figure 11] FIG. 4 is a cross-sectional view showing an example of a layer structure of the resin film for the all-solid-state battery shown in FIG. 3. [Figure 12] FIG. 4 is a cross-sectional view showing another example of the layer structure of the resin film for an all-solid-state battery shown in FIG. 3. [Figure 13] FIG. 11 is a cross-sectional view of a modified all-solid-state battery. [Figure 14]FIG. 13 is a cross-sectional view of an all-solid-state battery according to another modified example. [Figure 15] FIG. 13 is a cross-sectional view of yet another modified example of an all-solid-state battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, an all-solid-state battery according to one embodiment of the present invention will be described with reference to the drawings. In this specification, a numerical range indicated by "to" means "not less than" or "not more than." For example, the expression "2 to 15 mm" means 2 mm or more and 15 mm or less.
[0017] <1. Overall structure of all-solid-state battery> FIG. 1 is a plan view of the all-solid-state battery 10 of this embodiment. FIG. 2 is a cross-sectional view showing an example of the layer structure of the exterior members 21 and 22. FIG. 3 is a cross-sectional view taken along the line D2-D2 in FIG. 1. In the following, for convenience of explanation, unless otherwise specified, the up-down direction in FIG. 1 is referred to as "front-back", the left-right direction is referred to as "left-right", and the up-down direction in FIG. 3 is referred to as "up-down". However, the orientation of the all-solid-state battery 10 during use is not limited to this. In addition, the figures used in the following explanation may show characteristic parts in an enlarged manner for convenience of explanation, and the dimensional ratios of each component are not limited to those shown in the drawings.
[0018] The all-solid-state battery 10 is, for example, an all-solid-state lithium ion secondary battery, an all-solid-state sodium ion secondary battery, or an all-solid-state magnesium ion secondary battery. In this embodiment, the all-solid-state battery 10 is an all-solid-state lithium ion secondary battery. The all-solid-state battery 10 is used, for example, in electric vehicles such as electric vehicles and hybrid vehicles that are connected in series in large numbers and used at high voltage. The all-solid-state battery 10 includes an exterior body 20, a power storage element 30, an electrode terminal 80, and a terminal adhesive film 90.
[0019] The exterior body 20 has an internal space S1 and a peripheral seal portion 23. The energy storage element 30 is accommodated in the internal space S1 of the exterior body 20. One end of the electrode terminal 80 is joined to the energy storage element 30, and the other end protrudes outward from the peripheral seal portion 23 of the exterior body 20. A portion of the area between the one end and the other end of the electrode terminal 80 is fused to the peripheral seal portion 23 via an adhesive film 90 for terminals.
[0020] The exterior body 20 includes a container 20A. The container 20A includes exterior members 21 and 22. In a plan view, the exterior members 21 and 22 are heat-sealed and fused to each other at the outer periphery of the container 20A, thereby forming a peripheral seal portion 23. The peripheral seal portion 23 forms an internal space S1 of the container 20A that is isolated from the external space. The peripheral seal portion 23 defines the periphery of the internal space S1 of the container 20A. Note that the heat seal mode referred to here may be heat fusion from a heat source, ultrasonic fusion, or the like. In any case, the peripheral seal portion 23 refers to a portion where the exterior members 21 and 22 are fused and integrated. Note that the portion of the peripheral seal portion 23 that sandwiches the electrode terminal 80 and the terminal adhesive film 90 is an integrated portion of the exterior member 22, the electrode terminal 80, the pair of terminal adhesive films 90, and the exterior member 21. In the portion of the peripheral seal portion 23 that sandwiches only the pair of adhesive films 90 for terminals, the exterior member 22, the pair of adhesive films 90 for terminals, and the exterior member 21 are integrated.
[0021] The exterior members 21 and 22 are composed of, for example, a resin molded product or a film. The resin molded product referred to here can be manufactured by a method such as injection molding, compressed air molding, vacuum molding, or blow molding, and in-mold molding may be performed to impart design and functionality. The type of resin may be polyolefin, polyester, nylon, ABS, or the like. The film referred to here is, for example, a resin film that can be manufactured by a method such as an inflation method or a T-die method, or a film in which such a resin film is laminated on a metal foil. The film referred to here may or may not be stretched, and may be a single-layer film or a multilayer film. The multilayer film referred to here may be manufactured by a coating method, may be a film in which multiple films are bonded together with an adhesive, or may be manufactured by a multilayer extrusion method.
[0022] As described above, the exterior members 21 and 22 can be configured in various ways, but in this embodiment, as shown in FIG. 2, the laminate film is configured. The laminate film can be a laminated body in which the base layer 23A, the barrier layer 23B, and the heat-sealable resin layer 23C are laminated. The base layer 23A functions as a base material for the exterior members 21 and 22, and typically forms the outer layer side of the container 20A, and may be formed of a single layer or a multilayer of two or more layers of insulating resin layers such as polyesters such as polyethylene terephthalate and polybutylene terephthalate, and polyamides such as nylon. The barrier layer 23B has a function of preventing at least moisture from penetrating into the energy storage element 30 in addition to improving the strength of the exterior members 21 and 22, and is typically a metal layer made of aluminum alloy foil, stainless steel foil, titanium steel foil, steel sheet foil, or the like. The heat-sealable resin layer 23C is typically made of a heat-sealable resin such as polyolefins such as polypropylene, or polyesters such as polyethylene terephthalate or polybutylene terephthalate, and forms the innermost layer of the container 20A. The shape of the container 20A is not particularly limited, and may be, for example, a bag-like (pouch-like) shape. Possible bag-like shapes include a three-sided sealed type, a four-sided sealed type, a pillow type, and a gusset type. The container 20A may be composed of exterior members 21 and 22, or may be, for example, a metal can.
[0023] The electrode terminals 80 are metal terminals used for inputting and outputting power to and from the all-solid-state battery 10. The electrode terminals 80 are arranged separately at the left and right ends of the peripheral seal portion 23 of the container 20A, one of which constitutes a positive electrode side terminal and the other of which constitutes a negative electrode side terminal. One left and right end of each electrode terminal 80 is electrically connected to the positive electrode layer 40 or the negative electrode layer 50 (both see FIG. 3) of the energy storage element 30 in the internal space S1 of the container 20A, and the other end protrudes outward from the peripheral seal portion 23. The attachment positions of the two electrode terminals 80 constituting the terminals of the positive electrode layer 40 and the negative electrode layer 50 are not particularly limited, and may be arranged on the same side of the peripheral seal portion 23, for example.
[0024] The metal material constituting the electrode terminal 80 is, for example, aluminum, nickel, copper, etc. When the all-solid-state battery 10 is a lithium-ion secondary battery, the electrode terminal 80 connected to the positive electrode layer 40 is typically made of aluminum or the like, and the electrode terminal 80 connected to the negative electrode layer 50 is typically made of copper, nickel, etc.
[0025] The left-side electrode terminal 80 is sandwiched between the exterior members 21, 22 at the left end of the peripheral seal portion 23, with the terminal adhesive film 90 interposed therebetween. The right-side electrode terminal 80 is also sandwiched between the exterior members 21, 22 at the right end of the peripheral seal portion 23, with the terminal adhesive film 90 interposed therebetween.
[0026] The terminal adhesive film 90 is a so-called adhesive film, and is configured to adhere to both the exterior members 21, 22 and the electrode terminal 80 (metal). The terminal adhesive film 90 can fix the electrode terminal 80 and the innermost layer (thermally adhesive resin layer) of the exterior members 21, 22, even if they are made of different materials. The terminal adhesive film 90 is integrated by being fused and fixed to the electrode terminal 80 in advance, and the electrode terminal 80 to which the terminal adhesive film 90 is fixed is sandwiched between the exterior members 21, 22 and fused thereto, thereby integrating them.
[0027] <2. Energy storage element> <2-1. Overall composition> As shown in FIG. 3, the energy storage element 30 includes a positive electrode layer 40, a negative electrode layer 50, a solid electrolyte layer 60, and a resin film 70 for an all-solid-state battery (hereinafter referred to as "film 70"). The positive electrode layer 40 and the negative electrode layer 50 are alternately stacked on top of each other with the solid electrolyte layer 60 interposed therebetween. The all-solid-state battery 10 is charged and discharged by the exchange of lithium ions between the positive electrode layer 40 and the negative electrode layer 50 via the solid electrolyte layer 60. The number of positive electrode layers 40 and negative electrode layers 50 included in the energy storage element 30 can be selected arbitrarily. In this embodiment, the energy storage element 30 includes one positive electrode layer 40 and two negative electrode layers 50. The energy storage element 30 may have two or more positive electrode layers 40, or may have three or more negative electrode layers 50.
[0028] <2-2. Positive electrode layer> The positive electrode layer 40 includes a positive electrode current collector 41 and positive electrode active material layers 42 and 43 formed on a part of both sides of the positive electrode current collector 41. The positive electrode current collector 41 is preferably made of at least a material having high electrical conductivity. The material having high electrical conductivity is, for example, a metal or alloy containing at least one metal element of silver, palladium, gold, platinum, aluminum, copper, chromium, and nickel. The material constituting the positive electrode current collector 41 may be a nonmetal such as carbon. The shape of the positive electrode current collector 41 is, for example, a foil, a plate, a mesh, a nonwoven fabric, or a foam. In this embodiment, the shape of the positive electrode current collector 41 is a rectangular foil.
[0029] The positive electrode active material layers 42 and 43 contain a positive electrode active material capable of donating and receiving lithium ions and electrons. The positive electrode active material is not particularly limited as long as it is a material capable of reversibly desorbing and absorbing lithium ions and transporting electrons, and a known positive electrode active material applicable to the positive electrode layer of an all-solid-state lithium ion secondary battery can be used. The positive electrode active material layers 42 and 43 preferably contain a solid electrolyte 40A that donates and receives lithium ions to and from the positive electrode active material. The solid electrolyte 40A is not particularly limited as long as it has lithium ion conductivity, and a material generally used in all-solid-state lithium ion secondary batteries can be used. The concentration of the solid electrolyte 40A contained in the positive electrode active material layer 42 is preferably gradually increased toward the solid electrolyte layer 60 laminated on the positive electrode current collector 41. The concentration of the solid electrolyte 40A contained in the positive electrode active material layer 43 is preferably gradually increased toward the solid electrolyte layer 60 laminated under the positive electrode current collector 41.
[0030] In this embodiment, the positive electrode active material layers 42, 43 are formed on both sides of the positive electrode current collector 41, but this is not limited thereto, and either of the positive electrode active material layers 42, 43 may be formed on one side of the positive electrode current collector 41.
[0031] A terminal connection portion 41A where the positive electrode active material layers 42, 43 are not formed is formed on a part of both sides of the positive electrode current collector 41. The tip of the terminal connection portion 41A is located to the right of the right end portion of the negative electrode layer 50 and is exposed from the tip portion 70X of the film 70. The part of the terminal connection portion 41A exposed from the film 70 is electrically connected to, for example, the right electrode terminal 80 (see FIG. 1).
[0032] <2-3. Negative electrode layer> The negative electrode layer 50 includes a negative electrode current collector 51 and negative electrode active material layers 52 and 53 formed on both sides of the negative electrode current collector 51. The material constituting the negative electrode current collector 51 can be the material exemplified as the material constituting the positive electrode current collector 41. The shape of the negative electrode current collector 51 can be the shape exemplified as the shape of the positive electrode current collector 41. In this embodiment, the shape of the negative electrode current collector 51 is a rectangular foil shape. The concentration of the solid electrolyte 50A contained in the negative electrode active material layer 52 is preferably gradually increased toward the solid electrolyte layer 60 laminated on the negative electrode active material layer 52. The concentration of the solid electrolyte 50A contained in the negative electrode active material layer 53 is preferably gradually increased toward the solid electrolyte layer 60 laminated under the negative electrode active material layer 52.
[0033] The negative electrode active material layers 52 and 53 contain a negative electrode active material capable of donating and receiving lithium ions and electrons. The negative electrode active material is not particularly limited as long as it is a material that can reversibly release and absorb lithium ions and transport electrons, and any known negative electrode active material that can be applied to the negative electrode layer of an all-solid-state lithium ion secondary battery can be used.
[0034] In this embodiment, the negative electrode active material layers 52 and 53 are formed on both sides of the negative electrode current collector 51, but this is not limiting, and either of the negative electrode active material layers 52 and 53 may be formed on one side of the negative electrode current collector 51. For example, when the negative electrode layer 50 is formed in the lowest layer in the stacking direction (vertical direction) of the energy storage element 30, there is no opposing positive electrode layer 40 below the negative electrode layer 50 located in the lowest layer. For this reason, the negative electrode active material layer 52 may be formed only on one side of the negative electrode layer 50 located in the stacking direction.
[0035] A terminal connection portion 51A where the negative electrode active material layers 52, 53 are not formed is formed on a part of both sides of the negative electrode current collector 51. The tip of the terminal connection portion 51A is located to the left of the left end portion of the positive electrode layer 40. The terminal connection portion 51A is electrically connected to, for example, the left electrode terminal 80 (see FIG. 1).
[0036] <2-4. Solid electrolyte layer> The solid electrolyte layer 60 is composed of a material containing a solid electrolyte 60 A. The solid electrolyte is not particularly limited as long as it has lithium ion conductivity, and materials generally used in all-solid-state lithium ion secondary batteries can be used.
[0037] <2-5. Overview of resin films for solid-state batteries> If moisture penetrates into the inside of the all-solid-state battery 10 (electricity storage element 30), the performance of the all-solid-state battery 10 deteriorates. Therefore, the exterior members 21, 21 are provided with a barrier layer 23B (see FIG. 2). By providing the barrier layer 23B, it is possible to suppress the penetration of moisture from the outside of the barrier layer 23B. However, when the heat-sealable resin layer 23C of the exterior members 21, 22 is heat-sealed to seal the electricity storage element 30, the end face of the heat-sealable resin layer 23C is exposed to the outside. Therefore, there is a risk of moisture penetrating from the end face of the heat-sealable resin layer 23C. In addition, if the heat-sealable resin layer 23C of the exterior members 21, 22 absorbs water before sealing the electricity storage element 30 with the exterior members 21, 22, there is a risk that the moisture in the heat-sealable resin layer 23C will penetrate into the electricity storage element 30 after sealing the electricity storage element 30. When the solid electrolytes 40A, 50A, and 60A included in the elements constituting the all-solid-state battery 10 come into contact with moisture, gas such as hydrogen sulfide may be generated depending on the type of the solid electrolytes 40A, 50A, and 60A. This may increase the internal pressure of the exterior body 20. The all-solid-state battery 10 of this embodiment includes a film 70 capable of absorbing moisture that has entered the exterior body 20, moisture present in the exterior body 20, and gas generated from the all-solid-state battery 10.
[0038] The film 70 of this embodiment includes a first aspect and a second aspect. In the first aspect, the film 70 includes at least a water absorbing agent so that water vapor (moisture) does not come into contact with the solid electrolytes 40A, 50A, and 60A included in the elements constituting the all-solid-state battery 10 even when water vapor enters the inside of the exterior body 20 or when moisture is present inside the exterior body 20. In the second aspect of this embodiment, the film 70 includes at least a gas absorbing agent so as to absorb gases such as hydrogen sulfide generated when the solid electrolytes 40A, 50A, and 60A come into contact with water vapor.
[0039] The film 70 is disposed so as to be in contact with at least a portion of the solid electrolyte 40A of the positive electrode layer 40, the solid electrolyte 50A of the negative electrode layer 50, and the solid electrolyte 60A of the solid electrolyte layer 60. The location at which the film 70 is disposed can be arbitrarily selected as long as it is in contact with at least a portion of the solid electrolytes 40A, 50A, and 60A. Specific examples of the location at which the film 70 is disposed will be described below.
[0040] When the positive electrode layer 40 and the negative electrode layer 50 have substantially the same shape and area, there is a risk of short circuit due to contact between the outer peripheral end of the positive electrode layer 40 and the outer peripheral end of the negative electrode layer 50 in the process of hot pressing the energy storage element 30. For this reason, it is preferable that one of the positive electrode layer 40 and the negative electrode layer 50 has a smaller area than the other. The area of the positive electrode layer 40 is the area of the positive electrode active material layers 42 and 43 in a plan view. The area of the negative electrode layer 50 is the area of the negative electrode active material layers 52 and 53 in a plan view. In this embodiment, the area of the positive electrode active material layers 42 and 43 in a plan view is smaller than the area of the negative electrode active material layers 52 and 53. The shapes and areas of the positive electrode layer 40 and the negative electrode layer 50 may differ simply due to manufacturing errors.
[0041] 3, when one of the positive electrode layer 40 and the negative electrode layer 50 has a smaller area than the other, a step 200 is formed between the outer peripheral end of the positive electrode layer 40 and the outer peripheral end of the negative electrode layer 50. For this reason, when the energy storage element 30 is hot-pressed during the manufacture of the all-solid-state battery 10, for example, the outer peripheral end of the negative electrode layer 50 may be damaged at the step 200. In the energy storage element 30 of this embodiment, a film 70 is arranged to fill the step 200 in order to prevent such a situation from occurring.
[0042] In this embodiment, the energy storage element 30 has two films 70. The energy storage element 30 may have one film 70, or three or more films 70. In this embodiment, the film 70 is arranged along the outer periphery of the positive electrode layer 40 so as to contact the positive electrode layer 40 and the solid electrolyte layer 60. The film 70 may be arranged along at least a part of the outer periphery of the positive electrode layer 40. The tip portion 70X of the film 70 is located outside the outer edge of the negative electrode layer 50. In this embodiment, the film 70 is arranged along the entire periphery of the outer periphery of the positive electrode layer 40. Therefore, since the film 70 is arranged at a position corresponding to a wider range of the outer peripheral end portion of the negative electrode layer 50, the negative electrode layer 50 is less likely to be damaged during the manufacture of the energy storage element 30.
[0043] FIG. 4 is a plan view of the film 70. The shape of the film 70 can be selected arbitrarily. In this embodiment, the shape of the film 70 is a frame shape. The outer shape of the film 70 is rectangular. The outer shape of the film 70 may be a square or a polygon having pentagons or more sides. A hole 70A penetrating the film 70 is formed approximately in the center of the film 70. The inner shape of the hole 70A is approximately the same as the outer shape of the positive electrode active material layers 42, 43. The area of the hole 70A is slightly larger than the area of the positive electrode active material layers 42, 43.
[0044] FIG. 5 is a cross-sectional view showing another example of the arrangement of the film 70. In the example shown in FIG. 5, the areas of the positive electrode layer 40, the negative electrode layer 50, and the solid electrolyte layer 60 are substantially equal. Therefore, the side surface of the energy storage element 30 is substantially flush. In the example shown in FIG. 5, the film 70 is arranged to cover almost the entire side surface of the energy storage element 30 so as to contact the positive electrode layer 40, the negative electrode layer 50, and the solid electrolyte layer 60. In the example shown in FIG. 5, the shape of the film 70 does not need to be frame-like, and may be a sheet-like shape without holes. Note that the solid electrolytes 40A, 50A, and 60A are not shown in FIG. 5.
[0045] FIG. 6 is a cross-sectional view showing yet another example of the arrangement of the film 70. In the example shown in FIG. 6, the area of the positive electrode layer 40 is smaller than the area of the negative electrode layer 50. In the example shown in FIG. 6, the film 70 is arranged along the outer contour of the positive electrode layer 40. The tip portion 70X of the film 70 is substantially in the same position as the outer edge of the negative electrode layer 50. The tip portion 70X of the film 70 may be located inside the outer edge of the negative electrode layer 50. Note that the solid electrolytes 40A, 50A, and 60A are not shown in FIG. 6.
[0046] Film 70 may be disposed at any position inside barrier layer 23B of exterior members 21, 22, so long as it is in contact with at least a portion of solid electrolytes 40A, 50A, 60A included in the elements constituting energy storage element 30. In this embodiment, inside barrier layer 23B is the side opposite base layer 23A with respect to barrier layer 23B in the direction in which layers 23A to 23C of exterior members 21, 22 are stacked.
[0047] As shown in FIG. 2, the film 70 can also be used as the heat-sealable resin layer 23C of the exterior members 21 and 22. The film 70 can also be used as an adhesive layer between the barrier layer 23B and the heat-sealable resin layer 23C. When the film 70 is used as an adhesive layer between the barrier layer 23B and the heat-sealable resin layer 23C, a part of the film 70 is exposed between the barrier layer 23B and the heat-sealable resin layer 23C so as to be in contact with the energy storage element 30. The film 70 can also be used as an adhesive film interposed between the heat-sealable resin layers 23C facing each other at a position where the heat-sealable resin layers 23C of the exterior members 21 and 22 are heat-sealed to each other. When the film 70 is used as an adhesive film, if the internal pressure of the exterior body 20 increases due to gas generation from the energy storage element 30, the part of the heat-sealable resin layer 23C where the film 70 is interposed peels off, and the gas is released to the outside.
[0048] 7, the film 70 is disposed between the exterior members 21, 22 and the energy storage element 30 so as to cover substantially the entire upper and lower surfaces of the energy storage element 30. The film 70 and the inner surfaces (thermally adhesive resin layer 23C) of the exterior members 21, 22 may or may not be joined together.
[0049] 8, film 70 is disposed between exterior members 21, 22 and energy storage element 30 so as to cover substantially the entire side surface of energy storage element 30. Film 70 and the inner surfaces (thermally adhesive resin layer 23C) of exterior members 21, 22 may or may not be joined together.
[0050] 9, the film 70 is disposed between the exterior members 21, 22 and the energy storage element 30 so as to cover substantially the entirety of the energy storage element 30. The film 70 and the inner surfaces (thermally adhesive resin layer 23C) of the exterior members 21, 22 may or may not be joined together.
[0051] 10, the film 70 is used as a terminal adhesive film 90. Since the end faces of the terminal adhesive film 90 are exposed to the outside, there is a risk of moisture penetrating from the end faces of the terminal adhesive film 90. In addition, if the terminal adhesive film 90 absorbs water before being interposed between the electrode terminal 80 and the exterior members 21, 22, there is a risk that the moisture in the terminal adhesive film 90 will penetrate into the energy storage element 30 after the terminal adhesive film 90 is interposed between the electrode terminal 80 and the exterior members 21, 22.
[0052] By using the film 70 of the first embodiment as the adhesive film 90 for the terminal, it is possible to effectively prevent moisture from entering from the end of the adhesive film 90 for the terminal, and moisture contained in the adhesive film 90 for the terminal from entering the electric storage element 30. That is, in the all-solid-state battery 10 including the film 70 of the first embodiment, since the film 70 contains a water absorbing agent, the film 70 absorbs and holds the moisture that has entered from the adhesive film 90 for the terminal, thereby preventing moisture from reaching the electric storage element 30. In addition, by using the film 70 of the second embodiment as the adhesive film 90 for the terminal, for example, when the electric storage element 30 is an all-solid-state battery, it is possible to effectively absorb gas such as hydrogen sulfide generated by contact between the solid electrolyte layer contained in the element constituting the all-solid-state battery and moisture. That is, in the all-solid-state battery 10 including the film 70 of the second embodiment, since the film 70 contains a gas absorbent, gas such as hydrogen sulfide generated from the electric storage element 30 is absorbed by the film 70. Therefore, gas such as hydrogen sulfide is less likely to be released to the outside.
[0053] <2-6. Specific configuration of resin film for all-solid-state batteries> In the first aspect of the film 70, the moisture to be absorbed is gaseous and / or liquid moisture. As described later, the resin film for an all-solid-state battery according to the first aspect of the present embodiment can also absorb sulfur-based gases as necessary. Examples of sulfur-based gases include hydrogen sulfide, dimethyl sulfide, methyl mercaptan, and sulfur oxides represented by SOx. The moisture to be absorbed generates various outgases when absorbed in, for example, a solid electrolyte type lithium ion battery, and the sulfur-based gas is a component of the outgases (for example, generated when the all-solid-state battery 10 is an all-solid-state battery using a sulfide-based inorganic solid electrolyte or a lithium secondary battery using lithium sulfur in the positive electrode).
[0054] The film 70 of this embodiment may be composed of a single layer, for example, as shown in Fig. 3, or may be composed of two or more layers, for example, as shown in Fig. 11 and Fig. 12. Fig. 11 shows the film 70 composed of a laminate in which a first layer 71 and a second layer 72 are laminated. Fig. 12 shows the film 70 composed of a laminate in which a second layer 72, a first layer 71, and a third layer 73 are laminated in this order.
[0055] In the first embodiment, when the film 70 is composed of two or more layers, at least one of the two or more layers may contain a water absorbing agent. In this embodiment, the layer containing a water absorbing agent may be referred to as a "water absorbing layer". Specific examples of the lamination structure of the film 70 according to the first embodiment include a lamination structure in which the first layer 71 on the exterior members 21 and 22 side is a water absorbing layer, and the second layer 72 on the power storage element 30 side is a layer that does not contain a water absorbing agent, as shown in FIG. 11. Also, for example, in FIG. 12, a lamination structure in which the first layer 71 located in the middle is a water absorbing layer, and the second layer 72 on the power storage element 30 side and the third layer 73 on the exterior members 21 and 22 side are layers that do not contain a water absorbing agent; and a lamination structure in which at least one of the first layer 71 and the third layer 73 is a water absorbing layer, and the second layer 72 is a layer that does not contain a water absorbing agent.
[0056] In the second aspect, when the film 70 is composed of two or more layers, at least one of the two or more layers may contain a gas absorbent. The gas absorbent is, for example, at least one of a sulfur-based gas absorbent, a carbon dioxide absorbent, and an oxygen absorbent. In this embodiment, the second aspect of the film 70 will be described using a case where the gas absorbent is a sulfur-based gas absorbent as an example. Specific examples of the laminated structure of the film 70 according to the second aspect include, for example, a laminated structure in which the first layer 71 on the exterior members 21 and 22 side is a sulfur-based gas absorbing layer and the second layer 72 on the energy storage element 30 side is a layer that does not contain a sulfur-based gas absorbent in FIG. 11; and a laminated structure in which the first layer 71 on the exterior members 21 and 22 side is a layer that does not contain a sulfur-based gas absorbing layer and the second layer 72 on the energy storage element 30 side is a layer that contains a sulfur-based gas absorbent. 12, for example, the laminated structure may include a laminated structure in which the first layer 71 located in the middle is a sulfur-based gas absorbing layer, and the second layer 72 on the side of the energy storage element 30 and the third layer 73 on the side of the exterior members 21 and 22 are layers that do not contain a sulfur-based gas absorbent; a laminated structure in which at least one of the first layer 71 and the third layer 73 is a sulfur-based gas absorbing layer, and the second layer 72 is a layer that does not contain a sulfur-based gas absorbent; a laminated structure in which the first layer 71 located in the middle is a layer that does not contain a sulfur-based gas absorbing layer, and the second layer 72 on the side of the energy storage element 30 and the third layer 73 on the side of the exterior members 21 and 22 are layers that contain a sulfur-based gas absorbent; and a laminated structure in which at least one of the first layer 71 and the third layer 73 is a layer that does not contain a sulfur-based gas absorbing layer, and the second layer 72 is a layer that contains a sulfur-based gas absorbent. Since hydrogen sulfide gas is generated from the energy storage element 30, it is preferable that the second layer 72 located on the side of the energy storage element 30 is a sulfur-based gas absorbing layer.
[0057] In the first embodiment, it is preferable that one or both sides of the film 70 have thermal adhesion. When the film 70 according to the first embodiment is bonded to at least one of the positive electrode layer 40, the negative electrode layer 50, and the solid electrolyte layer 60, it is preferable to increase the thermal adhesion of the film 70. For example, when the film 70 is composed of three or more layers, it is preferable that the layer located on the surface (the second layer 72 and the third layer 73 in FIG. 12) contains a thermal adhesion resin. In addition, from the viewpoint of suppressing the decrease in the thermal adhesion of the layer located on the surface, it is preferable that the layer located on the surface does not contain a water absorbing agent (particularly an inorganic water absorbing agent). In the all-solid-state battery 10, from the viewpoint of more suitably exhibiting the water absorption performance of the water absorption layer of the film 70, it is preferable that the water absorption layer is provided between the layers located on the surface. This is because if the water absorption layer is located on the surface, it absorbs moisture in the air before the all-solid-state battery 10 is manufactured, and the water absorption performance of the water absorption layer is likely to decrease. In the all-solid-state battery 10, it is also preferable that the water absorption layer is the third layer 73 located on the side of the exterior members 21, 22. This is because the third layer 73 is close to the exterior members 21, 22 and easily absorbs moisture that has infiltrated from the exterior members 21, 22 side. In the all-solid-state battery 10, it is also preferable that the water absorption layer is the second layer 72 located on the side of the energy storage element 30. This is because the second layer 72 is close to the energy storage element 30 and easily absorbs moisture contained in the energy storage element 30.
[0058] In the second embodiment, it is also preferable that one or both sides of the film 70 have heat fusion properties. When the film 70 according to the second embodiment is bonded to at least one of the positive electrode layer 40, the negative electrode layer 50, and the solid electrolyte layer 60, it is preferable to increase the heat fusion properties of the film 70. Therefore, for example, when the film 70 is composed of three or more layers, it is preferable that the layer located on the surface (the second layer 72 and the third layer 73 in FIG. 12) contains a heat fusion resin. Moreover, from the viewpoint of suppressing a decrease in the heat fusion properties of the layer located on the surface, it is preferable that the layer located on the surface does not contain a sulfur-based gas absorbent.
[0059] The film 70 according to the first embodiment may further contain a sulfur-based gas absorbent, which will be described later, in addition to the water absorbing agent. In this embodiment, the layer containing the sulfur-based gas absorbent may be referred to as a "sulfur-based gas absorbing layer". When the sulfur-based gas absorbent is contained, the sulfur-based gas absorbent may be contained in the water absorbing layer, or may be contained in a layer that does not contain a water absorbing agent. When the film 70 is composed of two or more layers, it is preferable that the sulfur-based gas absorbent is contained in a layer that does not contain a water absorbing agent to constitute the sulfur-based gas absorbing layer. Concerns due to the inclusion of multiple types of particles in a single layer include that the particles are difficult to disperse during the film formation of the film 70, holes are formed in the film, and the strength of the film 70 varies depending on the location. In addition, when the amount of particles contained in a single layer exceeds a certain amount, the film's elongation and strength decrease, and there is a concern that the film may easily break at the corners of the battery. If the amounts are small, these concerns are unlikely to arise even if the water absorbing agent and the sulfur-based gas absorbent are contained in a single layer. However, in order to maintain the water absorption effect and the sulfur-based gas absorption effect for a long period of time, it is preferable that the water absorption layer and the sulfur-based gas absorbing layer are separate layers.
[0060] When the film 70 according to the first embodiment is composed of two or more layers, a specific example of the laminated structure of the film 70 is, for example, a laminated structure in which the first layer 71 is a water-absorbing layer and the second layer 72 is a sulfur-based gas absorbing layer in FIG. 11. Also, for example, in FIG. 12, a laminated structure in which the first layer 71 is a water-absorbing layer and at least one of the second layer 72 and the third layer 73 is a sulfur-based gas absorbing layer; a laminated structure in which at least one of the first layer 71 and the third layer 73 is a water-absorbing layer and the second layer 72 is a sulfur-based gas absorbing layer, and the like are included. Since hydrogen sulfide gas is generated from the energy storage element 30, it is preferable that the second layer 72 located on the energy storage element 30 side is a sulfur-based gas absorbing layer. In addition, as described above, since it is preferable that the water-absorbing layer is provided between layers located on the surface, among these, a laminated structure in which the first layer 71 located between the second layer 72 and the third layer 73 is a water-absorbing layer and the second layer 72 located on the energy storage element 30 side is a sulfur-based gas absorbing layer is the most preferable.
[0061] Moreover, the film 70 according to the second embodiment may further contain a water absorbing agent, which will be described later, in addition to the sulfur-based gas absorbent. As described above, in the present embodiment, the layer containing the water absorbing agent may be referred to as a "water absorbing layer". When the water absorbing agent is contained, the water absorbing agent may be contained in the sulfur-based gas absorbing layer, or may be contained in a layer that does not contain the water absorbing agent. When the film 70 according to the second embodiment is composed of two or more layers, it is preferable that the water absorbing agent is contained in a layer that does not contain the sulfur-based gas absorbent to constitute the water absorbing layer. Concerns due to the inclusion of multiple types of particles in a single layer include that the particles are difficult to disperse during the film formation of the film 70, holes are formed in the film, and the strength of the film 70 varies depending on the location. In addition, when the amount of particles contained in a single layer exceeds a certain amount, the film's elongation and strength decrease, and there is a concern that the film may be easily torn at the corners of the battery. If the amounts are small, these concerns are unlikely to arise even if the water absorbing agent and the sulfur-based gas absorbent are contained in a single layer. However, in order to maintain the water absorption effect and the sulfur-based gas absorption effect for a long period of time, it is preferable that the water absorption layer and the sulfur-based gas absorbing layer are separate layers.
[0062] When the film 70 according to the second embodiment is composed of two or more layers, a specific example of the laminated structure of the film 70 is, for example, a laminated structure in which the first layer 71 is a sulfur-based gas absorbing layer and the second layer 72 is a water absorbing layer in FIG. 11. Also, for example, in FIG. 12, a laminated structure in which the first layer 71 is a sulfur-based gas absorbing layer and at least one of the second layer 72 and the third layer 73 is a water absorbing layer; a laminated structure in which at least one of the first layer 71 and the third layer 73 is a sulfur-based gas absorbing layer and the second layer 72 is a water absorbing layer, and the like are included. In the all-solid-state battery 10, from the viewpoint of more suitably exerting the water absorbing performance of the water absorbing layer of the film 70, it is preferable that the water absorbing layer is provided between layers located on the surface. This is because if the water absorbing layer is located on the surface, it will absorb moisture in the air before the all-solid-state battery 10 is manufactured, and the water absorbing performance of the water absorbing layer is likely to decrease. A laminated structure in which the first layer 71 located between the second layer 72 and the third layer 73 is a water absorption layer described later, and the second layer 72 located on the electricity storage element 30 side is a sulfur-based gas absorption layer is the most preferable. In the all-solid-state battery 10, the water absorption layer is preferably the third layer 73 located on the exterior members 21 and 22 side. This is because the third layer 73 is close to the exterior members 21 and 22 and easily absorbs moisture that has infiltrated from the exterior members 21 and 22 side. In the all-solid-state battery 10, the water absorption layer is preferably the second layer 72 located on the electricity storage element 30 side. This is because the second layer 72 is close to the electricity storage element 30 and easily absorbs moisture contained in the electricity storage element 30.
[0063] In this embodiment, the resin contained in the film 70 is not particularly limited as long as it does not impair the effects of this embodiment. For example, it is preferably a thermoplastic resin, and more preferably a heat-sealable resin. Specific examples of the resin include thermoplastic resins such as polyester, polyolefin, polyamide, epoxy resin, acrylic resin, fluororesin, polyurethane, silicone resin, and phenolic resin, and modified products of these resins. The resin forming the film 70 may be a copolymer of these resins or a modified product of the copolymer. Furthermore, it may be a mixture of these resins. Among these, heat-sealable resins such as polyester and polyolefin are preferred.
[0064] Specific examples of polyesters include polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polyethylene isophthalate, and copolymerized polyesters. Examples of copolymerized polyesters include copolymerized polyesters in which ethylene terephthalate is the main repeating unit. Specific examples of polyesters include copolymerized polyesters in which ethylene terephthalate is the main repeating unit and is polymerized with ethylene isophthalate (hereinafter abbreviated as polyethylene (terephthalate / isophthalate)), polyethylene (terephthalate / adipate), polyethylene (terephthalate / sodium sulfoisophthalate), polyethylene (terephthalate / sodium isophthalate), polyethylene (terephthalate / phenyl-dicarboxylate), and polyethylene (terephthalate / decane dicarboxylate). These polyesters may be used alone or in combination of two or more. Among these, polybutylene terephthalate is particularly preferable from the viewpoint of increasing heat resistance and pressure resistance (for example, reduction in insulation when sealing the all-solid-state battery 10 element 4 with the exterior members 21 and 22 (due to crushing due to heat sealing)).
[0065] Specific examples of polyolefins include polyethylenes such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, and linear low-density polyethylene; ethylene-α-olefin copolymers; polypropylenes such as homopolypropylene, block copolymers of polypropylene (e.g., block copolymers of propylene and ethylene), and random copolymers of polypropylene (e.g., random copolymers of propylene and ethylene); propylene-α-olefin copolymers; and ethylene-butene-propylene terpolymers. When the polyolefin resin is a copolymer, it may be a block copolymer or a random copolymer. These polyolefin resins may be used alone or in combination of two or more. Among these, polypropylene is particularly preferred because of its excellent thermal fusion properties.
[0066] The resin contained in the film 70 preferably contains a resin containing a polyolefin skeleton as a main component, more preferably contains polyolefin as a main component, and even more preferably contains polypropylene as a main component. Here, the main component means that the content of the resin component contained in the film 70 is, for example, 50% by mass or more, preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, even more preferably 90% by mass or more, even more preferably 95% by mass or more, even more preferably 98% by mass or more, and even more preferably 99% by mass or more. For example, the resin contained in the film 70 contains polypropylene as a main component means that the content of polypropylene of the resin component contained in the film 70 is, for example, 50% by mass or more, preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, even more preferably 90% by mass or more, even more preferably 95% by mass or more, even more preferably 98% by mass or more, and even more preferably 99% by mass or more.
[0067] The resin contained in the film 70 preferably contains polyester as a main component. Here, the main component means that the content of the resin component contained in the film 70 is, for example, 50% by mass or more, preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, even more preferably 90% by mass or more, even more preferably 95% by mass or more, even more preferably 98% by mass or more, and even more preferably 99% by mass or more. For example, the resin contained in the film 70 contains polyester as a main component means that the content of polyester of the resin component contained in the film 70 is, for example, 50% by mass or more, preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, even more preferably 90% by mass or more, even more preferably 95% by mass or more, even more preferably 98% by mass or more, and even more preferably 99% by mass or more.
[0068] When producing the film 70 of the present embodiment, a preformed resin film may be used as the film 70. Also, the resin forming the film 70 may be formed into a film by extrusion molding, coating, or the like, to form a resin film.
[0069] In this embodiment, the resin contained in the film 70 may contain an elastomer. The elastomer plays a role of ensuring the durability of the film 70 in a high-temperature environment while increasing its flexibility. Preferred elastomers include at least one thermoplastic elastomer selected from polyesters, polyamides, polyurethanes, polyolefins, polystyrenes, and polyethers, or thermoplastic elastomers that are copolymers of these. The content of the elastomer in the film 70 is not particularly limited as long as it can ensure the durability of the film 70 in a high-temperature environment while increasing its flexibility, and is, for example, about 0.1% by mass or more, preferably about 0.5% by mass or more, more preferably about 1.0% by mass or more, and even more preferably about 3.0% by mass or more. The content is, for example, about 10.0% by mass or less, about 8.0% by mass or less, or about 5.0% by mass or less. Preferred ranges of the content include about 0.1 to 10.0 mass%, about 0.1 to 8.0 mass%, about 0.1 to 5.0 mass%, about 0.5 to 10.0 mass%, about 0.5 to 8.0 mass%, about 0.5 to 5.0 mass%, about 1.0 to 10.0 mass%, about 1.0 to 8.0 mass%, about 1.0 to 5.0 mass%, about 3.0 to 10.0 mass%, about 3.0 to 8.0 mass%, and about 3.0 to 5.0 mass%.
[0070] The content of the resin contained in the film 70 according to the first embodiment is, for example, 99.9% by mass or more, preferably 99.5% by mass or more, and more preferably 99.0% by mass or more.
[0071] The content of the resin in the film 70 according to the second embodiment is, for example, 50% by mass or more, preferably 55% by mass or more, and more preferably 60% by mass or more.
[0072] The water absorbing agent contained in the film 70 according to the first embodiment is not particularly limited as long as it is dispersed in a resin film and exhibits water absorption. For example, an inorganic water absorbing agent can be suitably used from the viewpoint of stability over time in the all-solid-state battery 10. Specific examples of preferred inorganic water absorbing agents include calcium oxide, anhydrous magnesium sulfate, magnesium oxide, calcium chloride, zeolite, aluminum oxide, silica gel, alumina gel, and calcined alum. In general, inorganic chemical water absorbing agents among inorganic water absorbing agents have a higher water absorption effect than inorganic physical water absorbing agents, can reduce the content, and can easily achieve sufficient water absorption and heat fusion in a single layer. Among inorganic chemical water absorbing agents, calcium oxide, anhydrous magnesium sulfate, and magnesium oxide are particularly preferred because they have little re-release of moisture, high stability over time in a low humidity state inside the package, and have an absolute dry effect. The absolute dry effect refers to the effect of absorbing water until the relative humidity becomes close to 0%, and the humidity control effect refers to the effect of absorbing water when the humidity is high and releasing moisture when the humidity is low to keep the humidity constant. Furthermore, when the material is used in a high-temperature environment, such as for an all-solid-state battery, an inorganic chemical absorbent that re-releases moisture in a high temperature range is preferred.
[0073] In the first embodiment, examples of the resin contained in the water-absorbing layer include the same resins as those exemplified as the resin contained in the film 70.
[0074] In the first embodiment, the content of the resin in the water absorption layer of the film 70 is, for example, 50% by mass or more, preferably 55% by mass or more, and more preferably 60% by mass or more.
[0075] In the first embodiment, the content of the water absorbing agent contained in the film 70 is not particularly limited as long as the effect of the present embodiment is exhibited, and is preferably about 0.5 parts by mass or more, more preferably about 2 parts by mass or more, and even more preferably about 3 parts by mass or more, relative to 100 parts by mass of the resin contained in the film 70, and is also preferably about 50 parts by mass or less, more preferably about 45 parts by mass or less, and even more preferably 40 parts by mass or less. Preferred ranges of the content include about 0.5 to 50 parts by mass, about 0.5 to 45 parts by mass, about 0.5 to 40 parts by mass, about 2 to 50 parts by mass, about 2 to 45 parts by mass, about 2 to 40 parts by mass, about 3 to 50 parts by mass, about 3 to 45 parts by mass, and about 3 to 40 parts by mass. The content of the water absorbing agent contained in the water absorption layer of the film 70 is not particularly limited as long as the effect of this embodiment is achieved, and is preferably at least about 0.5 parts by mass, more preferably at least about 2 parts by mass, and even more preferably at least about 3 parts by mass, relative to 100 parts by mass of the resin contained in the water absorption layer, and is preferably not more than about 50 parts by mass, more preferably not more than about 45 parts by mass, and even more preferably not more than 40 parts by mass. Preferred ranges of the content include about 0.5 to 50 parts by mass, about 0.5 to 45 parts by mass, about 0.5 to 40 parts by mass, about 2 to 50 parts by mass, about 2 to 45 parts by mass, about 2 to 40 parts by mass, about 3 to 50 parts by mass, about 3 to 45 parts by mass, and about 3 to 40 parts by mass.
[0076] In the film 70 according to the first embodiment, the water absorbing agent is preferably contained in the water absorbing layer via a master batch obtained by melt blending the water absorbing agent with a resin. Specifically, the water absorbing agent is melt blended with a resin at a relatively high concentration to prepare a master batch. The obtained master batch is further mixed with a resin and formed into a film to form the water absorbing layer. The content of the water absorbing agent in the master batch is preferably about 20 to 90 mass %, more preferably about 30 to 70 mass %. Within the above range, it is easy to include a necessary and sufficient amount of the water absorbing agent in the water absorbing layer in a dispersed state.
[0077] As described above, the film 70 according to the first embodiment may further contain a sulfur-based gas absorbent in addition to the water absorbing agent. The sulfur-based gas absorbent preferably contains a sulfur-based gas physical absorbent and / or a sulfur-based gas chemical absorbent. By using various sulfur-based gas absorbents in combination, for example, by using a sulfur-based gas physical absorbent and a sulfur-based gas chemical absorbent in combination, it becomes possible to easily absorb various types of sulfur-based gases. The sulfur-based gas absorbent is used, for example, in the form of a powder. The maximum particle size of the sulfur-based gas absorbent is preferably 20 μm or less, and the number average particle size of the powder is preferably 0.1 μm or more and 15 μm or less. If the number average particle size is smaller than the above range, the sulfur-based gas absorbent is likely to aggregate, and if the number average particle size is larger than the above range, the homogeneity of the sulfur-based resin film for all-solid-state batteries may be poor, and the surface area of the sulfur-based gas absorbent may be reduced, resulting in poor sulfur-based gas absorption.
[0078] (Sulfur gas physical absorbent) The sulfur-based gas physical absorbent is a gas absorbent that has the function of physically absorbing the sulfur-based gas to be absorbed. The sulfur-based gas physical absorbent preferably contains one or more selected from the group consisting of hydrophobic zeolite, bentonite, and sepiolite having a SiO2 / Al2O3 molar ratio of 1 / 1 to 2000 / 1.
[0079] Hydrophobic zeolite is a zeolite with excellent absorption of low polarity molecules such as sulfur-based gases, and has a porous structure. In general, the higher the molar ratio of SiO2 / Al2O3, which is a component of zeolite, the higher the hydrophobicity. And, as the hydrophobicity increases, it becomes easier to absorb low polarity molecules such as sulfur-based gases, and conversely, it becomes difficult to absorb them because the affinity with highly polar molecules such as water decreases. The SiO2 / Al2O3 molar ratio of hydrophobic zeolite is preferably 30 / 1 to 10000 / 1, more preferably 35 / 1 to 9000 / 1, and even more preferably 40 / 1 to 8500 / 1. In addition, hydrophobic zeolite has high heat resistance and can maintain its absorption effect even when exposed to high temperatures of 230°C or more. In the present invention, hydrophobic zeolite with a molar ratio in the above range is preferably used from the balance between sulfur-based gas absorption ability and ease of availability.
[0080] Bentonite is an inorganic substance whose main component is the clay mineral montmorillonite, containing a large amount of layered aluminum phyllosilicate, and containing minerals such as quartz and feldspar as impurities. For example, there are Na-type bentonite that contains a large amount of Na+ ions, Ca-type bentonite that contains a large amount of Ca2+ ions, and activated bentonite that is artificially converted to Na-type by adding a few wt% of sodium carbonate to Ca-type bentonite.
[0081] Sepiolite is a clay mineral whose main component is hydrated magnesium silicate, and its general chemical composition is Mg8Si 12 O 30 It is represented by (OH2)4(OH)4·6-8H2O and has a porous structure. From the viewpoint of availability, the pH (3% suspension) is preferably 8.0-9.0, and more preferably 8.9-9.3.
[0082] (Sulfur gas chemical absorbent) The sulfur-based gas chemical absorbent is a gas absorbent that has the function of chemically absorbing or decomposing the sulfur-based gas of the gas to be absorbed. And, because it is chemically absorbed or decomposed, it is not easily affected by water, etc., and once absorbed, the sulfur-based gas molecules are not easily desorbed, so that it can be efficiently absorbed. In addition, the decomposition product is absorbed by the sulfur-based gas physical absorbent or the sulfur-based gas chemical absorbent. The sulfur-based gas chemical absorbent preferably contains one or more selected from the group consisting of inorganic matter carrying a metal oxide, glass mixed with a metal, and glass mixed with a metal ion. The metal oxide in the inorganic matter carrying a metal oxide preferably contains one or more selected from the group consisting of CuO, ZnO, and AgO. In addition, the inorganic matter to be supported is preferably an inorganic porous body such as zeolite. The metal in the glass containing a metal, or the metal species of the metal ions in the glass containing a metal ion, preferably includes one or more species selected from the group consisting of Ca, Mg, Na, Cu, Zn, Ag, Pt, Au, Fe, Al, and Ni.
[0083] In the first embodiment, the content of the sulfur-based gas absorbent in the film 70 is not particularly limited as long as it absorbs a sulfur-based gas, and is preferably at least about 0.1 part by mass, more preferably at least about 0.2 parts by mass, and even more preferably at least about 0.3 parts by mass, relative to 100 parts by mass of the resin contained in the film 70, and is preferably at most about 30 parts by mass, more preferably at most about 27 parts by mass, and even more preferably at most 25 parts by mass. Preferred ranges of the content include about 0.1 to 30 parts by mass, about 0.1 to 27 parts by mass, about 0.1 to 25 parts by mass, about 0.2 to 30 parts by mass, about 0.2 to 27 parts by mass, about 0.2 to 25 parts by mass, about 0.3 to 30 parts by mass, about 0.3 to 27 parts by mass, and about 0.3 to 25 parts by mass. The content of the sulfur-based gas absorbent contained in the sulfur-based gas absorbing layer of the film 70 is not particularly limited as long as it absorbs sulfur-based gases, and is preferably about 5 parts by mass or more, more preferably about 6 parts by mass or more, and even more preferably about 7 parts by mass or more, relative to 100 parts by mass of the resin contained in the sulfur-based gas absorbing layer. Also, it is preferably about 60 parts by mass or less, more preferably about 55 parts by mass or less, and even more preferably about 50 parts by mass or less, and about 30 parts by mass or less. Preferred ranges of the content include about 5 to 60 parts by mass, about 5 to 55 parts by mass, about 5 to 50 parts by mass, about 5 to 30 parts by mass, about 6 to 60 parts by mass, about 6 to 55 parts by mass, about 6 to 50 parts by mass, about 6 to 30 parts by mass, about 7 to 60 parts by mass, about 7 to 55 parts by mass, about 7 to 50 parts by mass, and about 7 to 30 parts by mass.
[0084] In the first embodiment, the content of the resin contained in the sulfur-based gas absorbing layer is, for example, 50% by mass or more, preferably 55% by mass or more, and more preferably 60% by mass or more.
[0085] In the first embodiment, the sulfur-based gas absorbent contained in the sulfur-based gas absorbing layer is preferably contained via a master batch in which the sulfur-based gas absorbent is melt-blended with a resin. Specifically, it is preferable to melt-blend the sulfur-based gas absorbent with a resin at a relatively high concentration to prepare a master batch, and then dry-blend the master batch with other components to obtain a desired concentration in the sulfur-based gas absorbing layer. The sulfur-based gas absorbent and the resin to be melt-blended may each be one type or two or more types. The content of the sulfur-based gas absorbent in the master batch is preferably about 20 to 90 mass%, more preferably about 30 to 70 mass%. Within the above range, it is easy to contain a necessary and sufficient amount of the sulfur-based gas absorbent in a dispersed state in the sulfur-based gas absorbing layer.
[0086] In the first embodiment, examples of the resin contained in the sulfur-based gas absorbing layer include the same resins as those exemplified as the resin contained in the water absorbing layer.
[0087] As described above, when the film 70 according to the first embodiment contains a sulfur-based gas absorbent, the sulfur-based gas absorbent may be contained in the water-absorbing layer, or may be contained in a layer that does not contain a water-absorbing agent. When the sulfur-based gas absorbent is contained in the water-absorbing layer, the water-absorbing layer also functions as a sulfur-based gas absorbing layer.
[0088] The film 70 according to the first embodiment may contain various plastic compounding agents and additives for the purpose of improving or modifying, for example, processability, heat resistance, weather resistance, mechanical properties, dimensional stability, oxidation resistance, slipperiness, release properties, flame retardancy, mold resistance, electrical properties, strength, etc. The content may be any amount from a trace amount to several tens of percent depending on the purpose. In the above, examples of common additives that may be contained include antiblocking agents, lubricants, crosslinking agents, antioxidants, ultraviolet absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, pigments, modifying resins, etc.
[0089] The thickness of the film 70 according to the first embodiment is not particularly limited as long as the effects of the present invention are exhibited, and is preferably about 10 μm or more, more preferably about 15 μm or more, and even more preferably about 20 μm or more, and is preferably about 1000 μm or less, more preferably about 900 μm or less, and even more preferably about 500 μm or less. Preferred ranges of the thickness include about 10 to 1000 μm, about 10 to 900 μm, about 10 to 500 μm, about 15 to 1000 μm, about 15 to 900 μm, about 15 to 500 μm, about 20 to 1000 μm, about 20 to 900 μm, and about 20 to 500 μm.
[0090] In the first embodiment, when the film 70 is composed of two or more layers, the thickness of each layer may be as described above for the film 70. For example, the thickness of the water absorbing layer is preferably about 5 μm or more, more preferably about 6 μm or more, and even more preferably about 7 μm or more, and is preferably about 500 μm or less, more preferably about 400 μm or less, and even more preferably about 300 μm or less, and preferred ranges for the thickness include about 5 to 500 μm, about 5 to 400 μm, about 5 to 300 μm, about 6 to 500 μm, about 6 to 400 μm, about 6 to 300 μm, about 7 to 500 μm, about 7 to 400 μm, and about 7 to 300 μm. The thickness of the sulfur-based gas absorbing layer is preferably about 5 μm or more, more preferably about 7 μm or more, and even more preferably about 10 μm or more, and is preferably about 500 μm or less, more preferably about 400 μm or less, and even more preferably about 300 μm or less. Preferred ranges of the thickness include about 5 to 500 μm, about 5 to 400 μm, about 5 to 300 μm, about 7 to 500 μm, about 7 to 400 μm, about 7 to 300 μm, about 10 to 500 μm, about 10 to 400 μm, and about 10 to 300 μm.
[0091] In the second embodiment, the sulfur-based gas absorbent preferably contains a sulfur-based gas physical absorbent and / or a sulfur-based gas chemical absorbent. By using various sulfur-based gas absorbents in combination, for example, by using a sulfur-based gas physical absorbent and a sulfur-based gas chemical absorbent in combination, it becomes possible to easily absorb various types of sulfur-based gases. The sulfur-based gas absorbent is used, for example, in the form of a powder. The maximum particle size of the sulfur-based gas absorbent is preferably 20 μm or less, and the number average particle size of the powder is preferably 0.1 μm or more, 1.0 μm or more, and is preferably 15 μm or less, 10 μm or less, or 8 μm or less, and preferred ranges include about 0.1 to 15 μm, about 0.1 to 10 μm, about 0.1 to 8 μm, about 1 to 15 μm, about 1 to 10 μm, and about 1 to 8 μm. If the number average particle diameter is smaller than the above range, the sulfur-based gas absorbent is likely to aggregate, and if the number average particle diameter is larger than the above range, the homogeneity of the sulfur-based resin film for all-solid-state batteries may be deteriorated, and the surface area of the sulfur-based gas absorbent may be reduced, resulting in poor sulfur-based gas absorption.
[0092] (Sulfur gas physical absorbent) The sulfur-based gas physical absorbent is a gas absorbent that has the function of physically absorbing the sulfur-based gas to be absorbed. The sulfur-based gas physical absorbent preferably contains one or more selected from the group consisting of hydrophobic zeolite, bentonite, and sepiolite having a SiO2 / Al2O3 molar ratio of 1 / 1 to 2000 / 1.
[0093] Specific examples of the hydrophobic zeolite, bentonite, and sepiolite are the same as those described in the first embodiment, and description thereof will be omitted.
[0094] (Sulfur gas chemical absorbent) The sulfur-based gas chemical absorbent is as described in the first embodiment, and the description thereof will be omitted.
[0095] Examples of the resin contained in the sulfur-based gas absorbing layer include the same resins as those exemplified as the resin contained in the film 70 .
[0096] In the second embodiment, the content of the sulfur-based gas absorbent in film 70 is not particularly limited as long as it absorbs a sulfur-based gas, and is preferably at least about 0.1 part by mass, more preferably at least about 0.2 parts by mass, and even more preferably at least about 0.3 parts by mass, relative to 100 parts by mass of the resin contained in film 70, and is preferably at most about 30 parts by mass, more preferably at most about 29 parts by mass, and even more preferably at most 28 parts by mass. Preferred ranges of the content include about 0.1 to 30 parts by mass, about 0.1 to 29 parts by mass, about 0.1 to 28 parts by mass, about 0.2 to 30 parts by mass, about 0.2 to 29 parts by mass, about 0.2 to 28 parts by mass, about 0.3 to 30 parts by mass, about 0.3 to 29 parts by mass, and about 0.3 to 28 parts by mass. The content of the sulfur-based gas absorbent contained in the sulfur-based gas absorbing layer of the film 70 is not particularly limited as long as it absorbs sulfur-based gases, and is preferably about 5 parts by mass or more, more preferably about 6 parts by mass or more, and even more preferably about 7 parts by mass or more, relative to 100 parts by mass of the resin contained in the sulfur-based gas absorbing layer. Also, it is preferably about 60 parts by mass or less, more preferably about 55 parts by mass or less, even more preferably about 50 parts by mass or less, and even more preferably about 30 parts by mass or less. Preferred ranges of the content include about 5 to 60 parts by mass, about 5 to 55 parts by mass, about 5 to 50 parts by mass, about 5 to 30 parts by mass, about 6 to 60 parts by mass, about 6 to 55 parts by mass, about 6 to 50 parts by mass, about 6 to 30 parts by mass, about 7 to 60 parts by mass, about 7 to 55 parts by mass, about 7 to 50 parts by mass, and about 7 to 30 parts by mass.
[0097] In the second embodiment, the content of the resin contained in the sulfur-based gas absorbing layer is, for example, 40 mass % or more, preferably 45 mass % or more, and further preferably 50 mass % or more.
[0098] In the second embodiment, the sulfur-based gas absorbent contained in the sulfur-based gas absorbing layer is preferably contained via a master batch in which the sulfur-based gas absorbent is melt-blended with a resin. Specifically, it is preferable to melt-blend the sulfur-based gas absorbent with a resin at a relatively high concentration to prepare a master batch, and then dry-blend the master batch with other components to obtain a desired concentration in the sulfur-based gas absorbing layer. The sulfur-based gas absorbent and the resin to be melt-blended may each be one type or two or more types. The content of the sulfur-based gas absorbent in the master batch is preferably about 20 to 90 mass%, more preferably about 30 to 70 mass%. Within the above range, it is easy to contain a necessary and sufficient amount of the sulfur-based gas absorbent in a dispersed state in the sulfur-based gas absorbing layer.
[0099] As described above, in the second embodiment, the film 70 may further include a water absorbing agent in addition to the sulfur-based gas absorbent. The water absorbing agent contained in the film 70 is not particularly limited as long as it is dispersed in a resin film and exhibits water absorption. For example, an inorganic water absorbing agent can be suitably used from the viewpoint of stability over time in the all-solid-state battery 10. Specific examples of preferred inorganic water absorbing agents include calcium oxide, anhydrous magnesium sulfate, magnesium oxide, calcium chloride, zeolite, aluminum oxide, silica gel, alumina gel, and burnt alum. In general, among inorganic water absorbing agents, inorganic chemical water absorbing agents have a higher water absorption effect than inorganic physical water absorbing agents, can reduce the content, and are easy to achieve sufficient water absorption and heat fusion in a single layer. Among inorganic chemical water absorbing agents, calcium oxide, anhydrous magnesium sulfate, and magnesium oxide are particularly preferred because they release less moisture again, have high stability over time in a low humidity state in the package, and have an absolute dry effect. The bone-drying effect refers to the effect of absorbing water until the relative humidity is close to 0%, and the humidity control effect refers to the effect of absorbing water when the humidity is high and releasing moisture when the humidity is low, thereby keeping the humidity constant. In addition, when used in a high-temperature environment, such as for an all-solid-state battery, an inorganic chemical absorbent with a high temperature range for re-releasing moisture is preferred.
[0100] In the second embodiment, the content of the water absorbing agent contained in the film 70 is not particularly limited as long as the effect of the present embodiment is exhibited, and is preferably about 0.5 parts by mass or more, more preferably about 2 parts by mass or more, and even more preferably about 3 parts by mass or more, relative to 100 parts by mass of the resin contained in the film 70, and is also preferably about 50 parts by mass or less, more preferably about 45 parts by mass or less, and even more preferably 40 parts by mass or less. Preferred ranges of the content include about 0.5 to 50 parts by mass, about 0.5 to 45 parts by mass, about 0.5 to 40 parts by mass, about 2 to 50 parts by mass, about 2 to 45 parts by mass, about 2 to 40 parts by mass, about 3 to 50 parts by mass, about 3 to 45 parts by mass, and about 3 to 40 parts by mass. The content of the water absorbing agent contained in the water absorption layer of the film 70 is not particularly limited as long as the effect of this embodiment is achieved, and is preferably at least about 0.5 parts by mass, more preferably at least about 2 parts by mass, and even more preferably at least about 3 parts by mass, relative to 100 parts by mass of the resin contained in the water absorption layer, and is preferably not more than about 50 parts by mass, more preferably not more than about 45 parts by mass, and even more preferably not more than 40 parts by mass. Preferred ranges of the content include about 0.5 to 50 parts by mass, about 0.5 to 45 parts by mass, about 0.5 to 40 parts by mass, about 2 to 50 parts by mass, about 2 to 45 parts by mass, about 2 to 40 parts by mass, about 3 to 50 parts by mass, about 3 to 45 parts by mass, and about 3 to 40 parts by mass.
[0101] In the film 70 according to the second embodiment, the water absorbing agent is preferably contained in the water absorbing layer via a master batch obtained by melt blending the water absorbing agent with a resin. Specifically, the water absorbing agent is melt blended with a resin at a relatively high concentration to prepare a master batch. The obtained master batch is further mixed with a resin and formed into a film to form the water absorbing layer. The content of the water absorbing agent in the master batch is preferably about 20 to 90% by mass, more preferably about 30 to 70% by mass. Within the above range, it is easy to include a necessary and sufficient amount of the water absorbing agent in the water absorbing layer in a dispersed state.
[0102] In the second embodiment, examples of the resin contained in the water absorbing layer include the same resins as those exemplified as the resin contained in the film 70.
[0103] In the second embodiment, the content of the resin in the water absorption layer of the film 70 is, for example, 50% by mass or more, preferably 55% by mass or more, and more preferably 60% by mass or more.
[0104] As described above, when the film 70 according to the second embodiment contains a water absorbing agent, the water absorbing agent may be contained in the sulfur-based gas absorbing layer, or may be contained in a layer that does not contain the sulfur-based gas absorbent. When the water absorbing agent is contained in the sulfur-based gas absorbing layer, the sulfur-based gas absorbing layer also functions as a water absorbing layer.
[0105] In the second embodiment, the film 70 may contain various plastic compounding agents and additives for the purpose of improving or modifying, for example, processability, heat resistance, weather resistance, mechanical properties, dimensional stability, oxidation resistance, slipperiness, release properties, flame retardancy, mold resistance, electrical properties, strength, etc. The content may be any amount ranging from a trace amount to several tens of percent depending on the purpose. In the above, examples of typical additives that may be contained include antiblocking agents, lubricants, crosslinking agents, antioxidants, ultraviolet absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, pigments, modifying resins, etc.
[0106] In the second embodiment, the thickness of the film 70 is not particularly limited as long as the effects of the present invention are achieved, and is preferably about 25 μm or more, more preferably about 30 μm or more, and even more preferably about 40 μm or more, and is preferably about 250 μm or less, more preferably about 240 μm or less, and even more preferably about 230 μm or less. Preferred ranges of the thickness include about 25 to 250 μm, about 25 to 240 μm, about 25 to 230 μm, about 30 to 250 μm, about 30 to 240 μm, about 30 to 230 μm, about 40 to 250 μm, about 40 to 240 μm, and about 40 to 230 μm.
[0107] In the second embodiment, when the film 70 is composed of two or more layers, the thickness of each layer may be as described above for the film 70. For example, the thickness of the sulfur-based gas absorbing layer is preferably about 10 μm or more, more preferably about 15 μm or more, and even more preferably about 20 μm or more, and is, for example, about 100 μm or less, preferably about 95 μm or less, more preferably about 90 μm or less, and even more preferably about 85 μm or less, and preferred ranges of the thickness include about 10 to 100 μm, about 10 to 95 μm, about 10 to 90 μm, about 10 to 85 μm, about 15 to 100 μm, about 15 to 95 μm, about 15 to 90 μm, about 15 to 85 μm, about 20 to 100 μm, about 20 to 95 μm, about 20 to 90 μm, and about 20 to 85 μm. The thickness of the water absorption layer is preferably about 5 μm or more, more preferably about 6 μm or more, and even more preferably about 7 μm or more, and is preferably about 60 μm or less, more preferably about 55 μm or less, and even more preferably about 50 μm or less. Preferred ranges for the thickness include about 5 to 60 μm, about 5 to 55 μm, about 5 to 50 μm, about 6 to 60 μm, about 6 to 55 μm, about 6 to 50 μm, about 7 to 60 μm, about 7 to 55 μm, and about 7 to 50 μm.
[0108] (Manufacturing method of film 70) In this embodiment, the method for producing the film 70 is not particularly limited as long as the film 70 can be obtained, and known or commonly used film-forming methods and lamination methods can be applied. The film 70 can be produced by known film-forming methods and / or lamination methods, such as an extrusion method or a co-extrusion method, a cast molding method, a T-die method, a cutting method, or an inflation method. When the film 70 is composed of two or more layers, for example, the films constituting each layer that have been produced in advance may be laminated via an adhesive layer, a molten resin composition may be laminated on a layer that has been produced in advance by extrusion or co-extrusion, a plurality of layers may be simultaneously produced and laminated by melt pressure bonding, or one or more resins may be applied and dried to coat another layer.
[0109] In the first embodiment, the layers constituting the film 70, such as the water-absorbing layer (sulfur-based gas absorbing layer), may be laminated by extrusion or co-extrusion using an extrusion coating method, or may be laminated via an adhesive layer after film formation using an inflation method or cast method. Even in the case of the extrusion coating method, they may be laminated via an adhesive layer as necessary. Alternatively, a film for the water-absorbing layer (or sulfur-based gas absorbing layer) that has been previously formed may be laminated and bonded via an adhesive layer laminated by an extrusion coating method, a dry lamination method, a non-solvent lamination method, or the like. Then, an aging treatment may be performed as necessary.
[0110] In the first embodiment, for example, when laminating a water-absorbing layer or the like by extrusion coating, first, the resin composition forming the layer such as the water-absorbing layer is heated and melted, and then expanded and stretched in the required width direction by a T-die to be extruded or co-extruded in a curtain shape, and the molten resin is allowed to flow down onto the surface to be laminated, and sandwiched between a rubber roll and a cooled metal roll, thereby forming a layer such as the water-absorbing layer, laminating it on the surface to be laminated, and adhering it to the surface to be laminated can be performed simultaneously. When laminating by extrusion coating, the melt flow rate (MFR) of the resin component contained in each layer is preferably 0.2 to 50 g / 10 min, more preferably 0.5 to 30 g / 10 min. If the MFR is smaller or larger than the above range, the processability is likely to be inferior. In this specification, the MFR is a value measured by a method based on JIS K7210.
[0111] In the first embodiment, the melt flow rate (MFR) of the resin component contained in each layer when the inflation method is used is preferably 0.2 to 10 g / 10 min, more preferably 0.2 to 9.5 g / 10 min. If the MFR is smaller or larger than the above range, the processability is likely to be poor.
[0112] In the second embodiment, the layers constituting the film 70, such as the sulfur-based gas absorbing layer (water absorbing layer), may be laminated by extrusion or co-extrusion using an extrusion coating method, or may be laminated via an adhesive layer after film formation using an inflation method or cast method. Even in the case of the extrusion coating method, they may be laminated via an adhesive layer as necessary. Alternatively, a film for a sulfur-based gas absorbing layer (or water absorbing layer) that has been previously formed may be laminated and bonded via an adhesive layer laminated by an extrusion coating method, a dry lamination method, a non-solvent lamination method, or the like. Then, an aging treatment may be performed as necessary.
[0113] In the second embodiment, for example, when laminating a sulfur-based gas absorbing layer or the like by extrusion coating, first, the resin composition forming the layer such as the sulfur-based gas absorbing layer is heated and melted, and then expanded and stretched in the required width direction by a T-die to be extruded or co-extruded in a curtain shape, and the molten resin is allowed to flow down onto the surface to be laminated, and sandwiched between a rubber roll and a cooled metal roll, so that the formation of the layer such as the sulfur-based gas absorbing layer and the lamination and adhesion to the surface to be laminated can be performed simultaneously. When laminating by extrusion coating, the melt flow rate (MFR) of the resin component contained in each layer is preferably 0.2 to 50 g / 10 min, more preferably 0.5 to 30 g / 10 min. If the MFR is smaller or larger than the above range, the processability is likely to be inferior. In this specification, the MFR is a value measured by a method based on JIS K7210.
[0114] In the second embodiment, the melt flow rate (MFR) of the resin component contained in each layer when the inflation method is used is preferably 0.2 to 10 g / 10 min, more preferably 0.2 to 9.5 g / 10 min. If the MFR is smaller or larger than the above range, the processability is likely to be poor.
[0115] In this embodiment, in order to improve the adhesion between the layers constituting the film 70, a desired surface treatment may be applied in advance to the surface of each layer as necessary. For example, a corona discharge treatment, an ozone treatment, a low-temperature plasma treatment using oxygen gas or nitrogen gas, a glow discharge treatment, an oxidation treatment using chemicals, or other pretreatment may be optionally performed to form a corona treatment layer, an ozone treatment layer, a plasma treatment layer, an oxidation treatment layer, or the like. Alternatively, various coating layers such as a primer coating layer, an undercoat coating layer, an anchor coating layer, an adhesive layer, and a vapor deposition anchor coating layer may be optionally formed on the surface to form a surface treatment layer. For the various coating layers, for example, a resin composition containing a polyester resin, a polyamide resin, a polyurethane resin, an epoxy resin, a phenol resin, a (meth)acrylic resin, a polyvinyl acetate resin, a polyolefin resin such as polyethylene or polypropylene, or a copolymer or modified resin thereof, or a cellulose resin, or the like, as the main component of the vehicle may be used.
[0116] In this embodiment, each layer constituting the film 70 can be further uniaxially or biaxially stretched by a conventionally known method using a tenter system, a tubular system, or the like, as necessary.
[0117] <3. Function and effects of all-solid-state batteries> The all-solid-state battery 10 includes a film 70. The film 70 includes a water absorbing agent. Therefore, the film 70 can absorb water vapor that has entered the exterior body 20 and moisture that is present in the exterior body 20. Therefore, it is possible to suppress the generation of gases such as hydrogen sulfide caused by contact between the solid electrolytes 40A, 50A, and 60A included in the elements that configure the all-solid-state battery 10 and water vapor (moisture).
[0118] The film 70 contains a sulfur-based gas absorbent. Therefore, for example, it can absorb hydrogen sulfide that is generated when the solid electrolytes 40A, 50A, and 60A included in the elements that configure the all-solid-state battery 10 come into contact with water vapor (moisture). Therefore, it is possible to suppress an excessive increase in the internal pressure of the exterior body 20.
[0119] <4. Modifications> The above-mentioned embodiments are examples of possible forms of the all-solid-state battery according to the present invention, and are not intended to limit the forms. The all-solid-state battery according to the present invention may take forms different from those exemplified in the embodiments. Examples of such forms include forms in which a part of the configuration of the embodiment is replaced, changed, or omitted, or a new configuration is added to the embodiment. Below, some examples of modified embodiments are shown.
[0120] <4-1> In the above embodiment, the film 70 of the second aspect may contain at least one of a carbon dioxide absorbent and an oxygen absorbent as the gas absorbent.
[0121] <4-2> In the example of the above embodiment shown in FIG. 3, the film 70 may be disposed so as to contact at least one of the solid electrolyte 50A of the anode layer 50 and the solid electrolyte 60A of the solid electrolyte layer 60.
[0122] <4-3> In the above embodiment, the area of the positive electrode current collector 41 in a plan view is smaller than the area of the negative electrode current collector 51, and the area of the positive electrode active material layers 42, 43 in a plan view is smaller than the area of the negative electrode active material layers 52, 53, but these size relationships may be reversed. That is, the area of the positive electrode current collector 41 in a plan view may be larger than the area of the negative electrode current collector 51, and the area of the positive electrode active material layers 42, 43 in a plan view may be larger than the area of the negative electrode active material layers 52, 53. In this modification, the film 70 is preferably disposed along at least a part of the outer periphery of the negative electrode layer 50 so as to be in contact with the negative electrode layer 50.
[0123] <4-4> In the above embodiment, it is possible to arbitrarily change the configuration of the exterior body 20. For example, the exterior body 20 may be configured by wrapping one exterior member 21 around the energy storage element 30 so that an opening is formed.
[0124] 13 to 15 are cross-sectional views of a modified all-solid-state battery 10X. In the all-solid-state battery 10X, one exterior member 21 is wrapped around the energy storage element 30 so as to form an opening, and a lid 100 is disposed so as to close the opening. The side surface of the lid 100 and the exterior member 21 are preferably joined by, for example, heat sealing.
[0125] The lid body 100 may be a metal molded product of any shape, or may be a resin molded product of any shape. When the lid body 100 is a metal molded product or a resin molded product, it is preferable that the material constituting the lid body 100 has a certain thickness so that the exterior body 20 is suppressed from deforming even when the all-solid-state batteries 10X are arranged in a stacked manner. The minimum value of the thickness of the material constituting the lid body 100 is, for example, 1.0 mm, more preferably 3 mm, and further preferably 4 mm. The maximum value of the thickness of the material constituting the lid body 100 is, for example, 10 mm, more preferably 8.0 mm, and further preferably 7.0 mm. The maximum value of the thickness of the material constituting the lid body 100 may be 10 mm or more. The preferred ranges of the thickness of the material constituting the lid body 100 are 1.0 mm to 10 mm, 1.0 mm to 8.0 mm, 1.0 mm to 7.0 mm, 3.0 mm to 10 mm, 3.0 mm to 8.0 mm, 3.0 mm to 7.0 mm, 4.0 mm to 10 mm, 4.0 mm to 8.0 mm, and 4.0 mm to 7.0 mm. In the present disclosure, when the lid body 100 is expressed as a metal molded product or a resin molded product, a film is not included as a material constituting the lid body 100. The film is, for example, a film defined by the JIS (Japanese Industrial Standards) [packaging terminology] standard. The film defined by the JIS [packaging terminology] standard is a plastic film having a thickness of less than 250 μm. The thickness of the material constituting the lid body 100 may vary depending on the part of the lid body 100. When the thickness of the material constituting the lid body 100 varies depending on the part of the lid body 100, the thickness of the material constituting the lid body 100 is the thickness of the thickest part.
[0126] The lid body 100 may be, for example, plate-shaped. When the lid body 100 is plate-shaped, it is preferable that the lid body 100 has a certain degree of thickness so that the exterior body 20 is prevented from deforming even when the all-solid-state batteries 10X are arranged in a stacked manner. From another perspective, when the lid body 100 is plate-shaped, it is preferable that the side surface of the lid body 100 has a certain degree of thickness so that the side surface of the lid body 100 and the exterior member 21 can be suitably heat-sealed. The minimum value of the thickness of the lid body 100 is, for example, 1.0 mm, more preferably 3 mm, and further preferably 4 mm. The maximum value of the thickness of the lid body 100 is, for example, 10 mm, more preferably 8.0 mm, and further preferably 7.0 mm. The maximum value of the thickness of the lid body 100 may be 10 mm or more. The preferred ranges of the thickness of the material constituting the lid body 100 are 1.0 mm to 10 mm, 1.0 mm to 8.0 mm, 1.0 mm to 7.0 mm, 3.0 mm to 10 mm, 3.0 mm to 8.0 mm, 3.0 mm to 7.0 mm, 4.0 mm to 10 mm, 4.0 mm to 8.0 mm, and 4.0 mm to 7.0 mm. In the present disclosure, when the lid body 100 is expressed as a plate-like shape, the film defined by the [Packaging Terminology] standard of the JIS (Japanese Industrial Standards) is not included as the material constituting the lid body 100. The thickness of the lid body 100 may vary depending on the part of the lid body 100. When the thickness of the lid body 100 varies depending on the part, the thickness of the lid body 100 is the thickness of the thickest part.
[0127] The lid 100 includes a first surface 100A facing the energy storage element 30, and a second surface 100B opposite the first surface 100A. A hole 100C is formed in the center of the lid 100, penetrating the first surface 100A and the second surface 100B.
[0128] 13, the film 70 is disposed between the exterior member 21 and the energy storage element 30 so as to cover substantially the entire upper and lower surfaces of the energy storage element 30. The film 70 contacts at least a portion of the solid electrolytes 40A, 50A, 60A contained in the elements constituting the energy storage element 30. The film 70 and the inner surface of the exterior member 21 (thermally adhesive resin layer 23C) may or may not be bonded to each other. At least a portion of the film 70 may be disposed between the exterior member 21 and the lid 100.
[0129] In the example shown in FIG. 14, the film 70 is disposed between the lid 100 and the energy storage element 30 so as to cover substantially the entire side surface of the energy storage element 30. The film 70 contacts at least a part of the solid electrolytes 40A, 50A, 60A included in the elements constituting the energy storage element 30. The film 70 and the first surface 100A of the lid 100 may be bonded or not bonded. The film 70 and the first surface 100A of the lid 100 may be in contact or may be spaced apart. The film 70 may be disposed between the exterior member 21 and the energy storage element 30 so as to cover substantially the entirety of the energy storage element 30. The film 70 and the inner surface (thermally adhesive resin layer 23C) of the exterior member 21 may be bonded or not bonded.
[0130] In the example shown in FIG. 15, the film 70 is used as the terminal adhesive film 90. The film 70 contacts at least a part of the solid electrolytes 40A, 50A, 60A included in the elements constituting the energy storage element 30. The film 70 is preferably disposed at least in the hole 100C of the lid body 100. The film 70 may be exposed from the hole 100C of the lid body 100. The all-solid-state battery 10X including the lid body 100 may have a risk of moisture intrusion from the hole 100C of the lid body 100. In the all-solid-state battery 10X including the film 70 of the first embodiment, since the film 70 contains a water absorbing agent, the film 70 absorbs and retains the moisture intrusion from the hole 100C of the lid body 100, and thus the moisture can be prevented from reaching the energy storage element 30. In the all-solid-state battery 10X including the film 70 of the second embodiment, the film 70 contains a gas absorbent, and therefore gas such as hydrogen sulfide generated from the energy storage element 30 is absorbed by the film 70. Therefore, gas such as hydrogen sulfide is less likely to be released to the outside through the hole 100C of the lid 100.
[0131] <5. Examples> The inventors of the present application manufactured all-solid-state batteries of Examples 1 to 3 and Comparative Examples 1 and 2, and performed tests to check for short-circuiting between the positive electrode layer and the negative electrode layer, and for expansion of the container. In the following, for the sake of convenience, the same elements as those in the embodiment may be denoted by the same reference numerals as those in the embodiment, among the elements constituting the all-solid-state batteries of the Examples and Comparative Examples.
[0132] <5-0. Manufacturing and testing methods for resin films for all-solid-state batteries> The inventors of the present application manufactured the film 70 used in the all-solid-state batteries of Examples 1 to 3 by the following procedure. The inventors of the present application prepared a master batch by dispersing a moisture absorbent powder in polypropylene using a twin-screw kneading extruder, and manufactured the film 70 by adjusting the cylinder rotation speed and take-up speed of the extruder using an inflation extruder to obtain a desired thickness.
[0133] The produced film 70 was cut into a frame of 3 cm square (width 5 mm), and a 2 cm square solid electrolyte layer 60 and the film 70 were placed on a 3 cm square negative electrode layer 50, and a 2.5 cm square positive electrode layer 40 was laminated thereon, and the whole was surface-pressed at a pressure of 100 MPa from the top and bottom. The surface pressing conditions were room temperature, room humidity, and a press holding time of 10 minutes. Next, the electrical conduction between the positive electrode layer 40 and the negative electrode layer 50 was confirmed with a multimeter. The multimeter used in this test was a 3154 DIGITAL MΩ HiTESTER manufactured by Hioki E.E. Co., Ltd. When the resistance value measured by the multimeter was 2000 MΩ or less, it was determined that there was no electrical conduction between the positive electrode layer 40 and the negative electrode layer 50.
[0134] Next, the energy storage element 30 was wrapped in 6 cm square exterior members 21, 22, and the four sides of the exterior members 21, 22 were heat sealed with a 7 mm seal bar so that the remaining rate of the heat-fusible resin layer 23C was 70%, and then the seal width was cut to 2 mm, obtaining a 5 cm square exterior body 20 housing the energy storage element 30. The exterior body 20 housing the energy storage element 30 was left in an environment of a temperature of 85°C and a humidity of 85% for 100 hours, and then the presence or absence of expansion of the exterior body 20 due to gas generation was visually confirmed. In this test, the film 70 used was left to stand in a vacuum oven (-50 MPa) for 24 hours and dried before the test (before installation).
[0135] <5-1. Example 1> The all-solid-state battery of Example 1 is the all-solid-state battery 10 of the embodiment. In the all-solid-state battery of Example 1, a film 70 is disposed as shown in Fig. 3. The film 70 has a first layer 71, a second layer 72, and a third layer 73 shown in Fig. 12. The specifications of the film 70 are as follows.
[0136] The material constituting the first layer 71 is polypropylene with a moisture absorbent added. The moisture absorption concentration of the first layer 71 is 20 wt %. The thickness of the first layer 71 is 30 μm. The material constituting the second layer 72 is polypropylene. The thickness of the second layer 72 is 10 μm. The material constituting the third layer 73 is polypropylene. The thickness of the third layer 73 is 10 μm. The overall moisture absorption concentration of the film 70 used in the all-solid-state battery 10 in Example 1 is 12 wt %.
[0137] <5-2. Example 2> The all-solid-state battery of Example 2 is the all-solid-state battery 10 of the embodiment. In the all-solid-state battery of Example 2, a film 70 is disposed as shown in Fig. 3. The film 70 is a single layer as shown in Fig. 3. The specifications of the film 70 are as follows.
[0138] The material constituting the film 70 is polypropylene with a moisture absorbent added. The moisture absorption concentration of the film 70 is 12 wt%. The thickness of the film 70 is 50 μm.
[0139] <5-3. Example 3> The all-solid-state battery of Example 3 is the all-solid-state battery 10 of the embodiment. In the all-solid-state battery of Example 3, a film 70 is disposed as shown in Fig. 3. The film 70 is a single layer as shown in Fig. 3. The specifications of the film 70 are as follows.
[0140] The material constituting the film 70 is polypropylene with a moisture absorbent added. The moisture absorption concentration of the film 70 is 24 wt%. The thickness of the film 70 is 100 μm.
[0141] <5-4. Comparative Example 1> The all-solid-state battery of Comparative Example 1 differs from the all-solid-state battery 10 of the embodiment in that it does not have the film 70, but the other configurations are the same as those of the all-solid-state battery 10 of the embodiment.
[0142] <5-5. Comparative Example 2> The all-solid-state battery of Comparative Example 2 differs from the all-solid-state battery 10 of the embodiment in that it has a polypropylene film instead of the film 70, and the other configurations are the same as those of the all-solid-state battery 10 of the embodiment. In the all-solid-state battery of Comparative Example 2, a polypropylene film is disposed in the same position as the film 70 in Fig. 3. The thickness of the polypropylene film is 50 µm.
[0143] <5-6. Test Results> In the all-solid-state batteries of Examples 1 to 3, no current flow was observed between the positive electrode layer 40 and the negative electrode layer 50. This is believed to be because, in the all-solid-state batteries of Examples 1 to 3, the film 70 was disposed between the positive electrode layer 40 and the negative electrode layer 50, and therefore the outer peripheral end of the negative electrode layer 50 was not damaged when pressed, and no short circuit occurred.
[0144] In the all-solid-state batteries of Examples 1 to 3, expansion of the exterior body 20 was not observed. This is considered to be because the all-solid-state batteries of Examples 1 to 3 have the film 70, and therefore water vapor that entered from the outside of the exterior body 20 was absorbed by the film 70, and the water vapor did not come into contact with the solid electrolyte, or a small amount of water vapor came into contact with the solid electrolyte.
[0145] In the all-solid-state battery of Comparative Example 1, electrical conduction was confirmed between the positive electrode layer 40 and the negative electrode layer 50. This is believed to be because the all-solid-state battery of Comparative Example 1 does not have a film between the positive electrode layer 40 and the negative electrode layer 50, and therefore the outer peripheral end of the negative electrode layer 50 was damaged when pressed, causing a short circuit.
[0146] In the all-solid-state battery of Comparative Example 1, expansion of the exterior body 20 was confirmed. This is considered to be because the all-solid-state battery of Comparative Example 1 does not have the film 70, and therefore water vapor entering from the outside of the exterior body 20 comes into contact with the solid electrolyte, generating gases such as hydrogen sulfide.
[0147] In the all-solid-state battery of Comparative Example 2, no current flow was observed between the positive electrode layer 40 and the negative electrode layer 50. This is believed to be because the all-solid-state battery of Comparative Example 2 had a polypropylene film disposed between the positive electrode layer 40 and the negative electrode layer 50, and therefore the outer peripheral end of the negative electrode layer 50 was not damaged when pressed, and no short circuit occurred.
[0148] In the all-solid-state battery of Comparative Example 2, expansion of the exterior body 20 was confirmed. This is believed to be because, in the all-solid-state battery of Comparative Example 2, the polypropylene film does not have gas absorption properties, and therefore, water vapor that entered from the outside of the exterior body 20 came into contact with the solid electrolyte, generating gases such as hydrogen sulfide.
[0149] [6. Additional Notes] A first aspect of the film 70 of this embodiment includes the following features.
[0150] Item 1A. A resin film for an all-solid-state battery, which is arranged so as to contact at least a part of a solid electrolyte contained in an element constituting an electric storage element of an all-solid-state battery, A resin film for solid-state batteries containing a water-absorbing agent. Item 2A. The resin film for an all-solid-state battery according to Item 1A, wherein the water absorbing agent is an inorganic water absorbing agent. Item 3A. The resin film for an all-solid-state battery according to Item 1A or 2A, wherein the water absorbing agent is at least one selected from the group consisting of calcium oxide, anhydrous magnesium sulfate, magnesium oxide, calcium chloride, zeolite, aluminum oxide, silica gel, alumina gel, and calcined alum. Item 4A. The resin film for an all-solid-state battery according to any one of Items 1A to 3A, wherein the content of the water absorbing agent is 0.1 parts by mass or more relative to 100 parts by mass of the resin contained in the resin film for an all-solid-state battery. Item 5A: The resin film for an all-solid-state battery according to any one of Items 1A to 4A, which is constituted of two or more layers. Item 6A. The resin film for an all-solid-state battery according to Item 5A, wherein at least one of the two or more layers contains the water absorbing agent and at least one of the layers contains a sulfur-based gas absorbing agent. Item 7A. The layer containing the water absorbing agent of the resin film for all-solid-state batteries contains 0.5 mass parts of the absorbent or more per 100 mass parts of resin. The resin film for all-solid-state batteries according to any one of Items 1A to 6A. Item 8A. The resin film for an all-solid-state battery according to any one of Items 1A to 7A, comprising a heat-sealable resin. Item 9A. The resin film for an all-solid-state battery according to Item 8A, wherein the heat-sealable resin comprises at least one selected from the group consisting of polyesters and polyolefins.
[0151] A second aspect of the film 70 of this embodiment includes the following. Item 1B. A resin film for an all-solid-state battery, which is arranged so as to contact at least a part of a solid electrolyte contained in an element constituting an electric storage element of an all-solid-state battery, A resin film for solid-state batteries containing a sulfur-based gas absorbent. Item 2B. The resin film for an all-solid-state battery according to item 1B, wherein the content of the sulfur-based gas absorbent is 0.1 parts by mass or more relative to 100 parts by mass of the resin contained in the resin film for an all-solid-state battery. Item 3B. The resin film for an all-solid-state battery according to Item 1B or 2B, wherein the sulfur-based gas absorbent has a maximum particle size of 20 μm or less and a number average particle size of 0.1 μm or more and 15 μm or less. Item 4B: The resin film for an all-solid-state battery according to any one of Items 1B to 3B, wherein the sulfur-based gas absorbent includes at least one selected from the group consisting of a sulfur-based gas chemical absorbent and a sulfur-based gas physical absorbent. Item 5B. The resin film for an all-solid-state battery according to Item 4B, wherein the sulfur-based gas physical absorbent includes at least one selected from the group consisting of hydrophobic zeolite having a SiO2 / Al2O3 molar ratio of 1 / 1 to 2000 / 1, bentonite, and sepiolite. Item 6B. The resin film for an all-solid-state battery according to Item 4B or 5B, wherein the sulfur-based gas chemical absorbent is a metal oxide or an inorganic material carrying or containing a metal or metal ion. Item 7B. The resin film for an all-solid-state battery according to Item 6B, wherein the metal oxide comprises at least one selected from the group consisting of CuO, ZnO, and AgO. Item 8B: The resin film for an all-solid-state battery according to Item 6B or 7B, wherein the metal species in the inorganic material carrying or containing the metal or metal ion is at least one selected from the group consisting of Ca, Mg, Na, Cu, Zn, Ag, Pt, Au, Fe, Al and Ni. Item 9B: The layer containing the sulfur-based gas absorbent of the resin film for all-solid-state batteries contains 5 mass parts of the sulfur-based gas absorbent or more per 100 mass parts of resin. The resin film for all-solid-state batteries according to any one of Items 1B to 8B. Item 10B: The resin film for an all-solid-state battery according to any one of items 1B to 9B, comprising a heat-sealable resin. Item 11B. The resin film for an all-solid-state battery according to Item 10B, wherein the heat-sealable resin comprises at least one selected from the group consisting of polyesters and polyolefins. [Explanation of symbols]
[0152] 10: All-solid-state battery 23C: Barrier layer 40A, 50A, 60A: Solid electrolyte 40: Positive electrode layer 50: Negative electrode layer 60: Solid electrolyte layer 70: Resin film for solid-state batteries
Claims
1. An electricity storage element including a solid electrolyte; a resin film for an all-solid-state battery arranged so as to contact at least a portion of the solid electrolyte; The resin film for an all-solid-state battery contains at least one of a water absorbing agent and a gas absorbing agent. All-solid-state battery.
2. A solid electrolyte layer containing the solid electrolyte, The resin film for an all-solid-state battery is disposed so as to be in contact with at least the solid electrolyte layer. The all-solid-state battery according to claim 1 .
3. a positive electrode layer including the solid electrolyte; The resin film for an all-solid-state battery is disposed so as to be in contact with at least the positive electrode layer. The all-solid-state battery according to claim 1 or 2.
4. a negative electrode layer including the solid electrolyte; The resin film for an all-solid-state battery is disposed so as to be in contact with at least the negative electrode layer. The all-solid-state battery according to claim 1 or 2.
5. The resin film for an all-solid-state battery has a frame shape surrounding the solid electrolyte. The all-solid-state battery according to claim 1 or 2.
6. An exterior body that seals the energy storage element is provided, The exterior body is formed of a film-like exterior member including a barrier layer, The resin film for an all-solid-state battery is disposed at least partially inside the barrier layer. The all-solid-state battery according to claim 1 or 2.
7. The resin film for an all-solid-state battery contains a sulfur-based gas absorbent, The sulfur-based gas absorbent includes at least one selected from the group consisting of a sulfur-based gas chemical absorbent and a sulfur-based gas physical absorbent. The all-solid-state battery according to claim 1 or 2.
8. The sulfur-based gas chemical absorbent is a metal oxide or an inorganic material carrying or containing a metal or metal ion. The all-solid-state battery according to claim 7.
Citation Information
Patent Citations
All-solid battery and its manufacturing method
JP2009193728A